Analisis Kapasitas Saluran Drainase pada Wilayah Padat Penduduk dengan Menggunakan Rational Modification Method - D.L. Pamuttu; J. Paresa; E. Yufri (Civil Engineering Department, Tadulako University, 2023)
Merauke City, as a city in a growth and development period, cannot be separated from various problems. The provision of inadequate city facilities and infrastructure is one of the factors in the situation, drainage, for example. Generally, drainage handling in Merauke City is not comprehensive, so it has yet to handle the problem of inundation or flooding entirely. In residential areas around Estuary 3, puddles or floods are often found whenever rain is high enough intensity. Given that the city of Merauke, including in a flat area or the absence of elevation differences, makes one of the causes of waterlogging or flooding. This study aims to determine the capacity of estuary drainage channels in 3 Merauke Regency to accommodate or drain planned flood discharge. The research method used in this study is the rational method. This study uses two analyses, namely hydrological analysis and hydraulics analysis, where hydrological analysis a carried out to determine planned flood discharge by calculating daily rainfall using probability distribution and hydraulics analysis to determine channel capacity discharge by calculating cross-sectional dimensions. Based on the results of the study shows that segment 1 to segment 10 has different capacity discharge (Qs) and flood discharge (Qr). Segment 1 is one of the channel segments capable of accommodating or draining planned flood discharge with a capacity discharge of 5.51